The Role of Emotional Intelligence in Financial Competence - Elanda, Yochi; Rizki, Ainur (Takaza Innovatix Labs Ltd., 2024)
This research explores the impact of emotional intelligence, personal financial management skills, and financial behavior on financial competence among employees of Bank Pembangunan Daerah Sulawesi Selatan. Employing a quantitative methodology with random sampling of 90 customers, data were collected through a structured questionnaire and analyzed using Smart PLS for structural equation modeling. The findings reveal that emotional intelligence significantly influences financial competence both directly and indirectly through personal financial management skills and financial behavior. Specifically, employees with higher emotional intelligence exhibit better financial management abilities and engage in positive financial behaviors, which in turn enhance their overall financial competence. The study highlights the critical role of emotional intelligence as a foundational skill in effective financial service delivery. These insights suggest that improving emotional and financial management skills among employees can lead to enhanced performance and greater customer satisfaction, thereby contributing to the bank's long-term success. The research emphasizes the need for integrated training programs within banking institutions to promote financial literacy and emotional intelligence, ultimately fostering sustainable growth in a competitive financial landscape.